To Study Serum Total Protein and Serum Albumin in Children with Grade III and Grade IV Protein Energy Malnutrition (Cases) and in Children with Grade I and Grade II Protein Energy Malnutrition (Controls) - Dehariya, RashmiEkka; Eske, Gunvant Singh (Asian Journal of Clinical Pediatrics and Neonatology, 2019)
Background: This was a hospital based case control study, conducted in the Nutrition Rehabilitation centre in Index Medical College Hospital & Research Centre, Indore, Department of Pediatrics. Subjects and Methods: Children with PEM grade I and II without any other pathological problem.The children admitted in the department. Results: In study group, majority of children had PEM grade III malnutrition while in control group, equal number of children had PEM grade I and grade II malnutrition. This table shows that majority of children in study group had lower level of serum protein levels as compared with control group, and there is progressive fall in its level as the severity of malnutrition increases. This table shows that majority of children in study group had lower level of serum albumin levels as compared with control group, and there is progressive fall in its level as the severity of malnutrition increases. Conclusion: The study concludes that estimation of serum T3, T4 and TSH levels in severely malnourished children admitted and co-relation with serum protein and serum albumin levels. To conclude, altered thyroid profile in PEM is perhaps a defense mechanism against excessive metabolic stimulation and energy consumption. The resultant hypometabolism protect the malnourished child with low calories reserve from an early death.